Continuity and discontinuity in the peopling of Europe one hundred fifty years of Neanderthal study - Condemi, Silvana; Weniger, Gerd-Christian (Springer eBooks., 2011)
Since the Western world first became aware of the existence of Neanderthals, this Pleistocene human has been a regular focus of interest among specialists and also among the general public. In fact, we know far more about Neanderthals than we do about any other extinct human population. Furthermore, over the past 150 years no other palaeospecies has been such a constant source of discussion and fierce debate among palaeoanthropologists and archaeologists. This book presents the status of our knowledge as well as the methods and techniques used to study this extinct population and it suggests perspectives for future research.